Molecular scale cure rate dependence of thermoset matrix polymers - Childers, Christopher H. (2016)
This manuscript demonstrates the molecular scale cure rate dependence of di-functional epoxide based thermoset polymers cured with amines. A series of cure heating ramp rates were used to determine the influence of ramp rate on the glass transition temperature (Tg) and sub-Tg transitions and the average free volume hole size in these systems. The networks were comprised of 3,3′-diaminodiphenyl sulfone (33DDS) and diglycidyl ether of bisphenol F (DGEBF) and were cured at ramp rates ranging from 0.5 to 20°C/min. Differential scanning calorimetry (DSC) and NIR spectroscopy were used to explore the cure ramp rate dependence of the polymer network growth, whereas broadband dielectric spectroscopy (BDS) and free volume hole size measurements were used to interrogate networks’ molecular level structural variations upon curing at variable heating ramp rates. It was found that although the Tg of the polymer matrices was similar, the NIR and DSC measurements revealed a strong correlation for how these networks grow in relation to the cure heating ramp rate. The free volume analysis and BDS results for the cured samples suggest differences in the molecular architecture of the matrix polymers due to cure heating rate dependence.